2022
DOI: 10.1200/jco.2022.40.28_suppl.068
|View full text |Cite
|
Sign up to set email alerts
|

Enrollment patterns and site-level predictors of Black participant recruitment to a multisite randomized clinical trial (RCT) of endocrine therapy adherence support.

Abstract: 68 Background: Accrual of racial and ethnic minority patients (pts) to clinical trials has been an ongoing challenge in research. Barriers exist at many levels of engagement including trial availability, screening biases, strict enrollment criteria, and structural racism. Lack of trial diversity has led to less generalizable medical evidence, suboptimal data for toxicity and efficacy of cancer treatments, poorer outcomes and continued mistrust by communities of color in research processes that exclude or marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other innovations in the structure of the clinical trials system will be necessary to truly foster diversity and representativeness, including decentralization of research to locations near patients of color 100 . In a recent analysis of accrual patterns by race for a large breast cancer cooperative group trial that oversamples Black women, we found that the most important site-level predictor of high accrual of Black patients was the proportion of Black residents in the zip code where the trial site was located 101 . Other key strategies, as outlined in a recent policy statement from the American Society of Clinical Oncology and Association of Community Cancer Centers, include education of the research workforce on equity, diversity, and inclusion issues and diversifying the workforce itself to reflect the communities in which cancer research is performed 102 .…”
Section: Five Keys To Impactful Breast Cancer Equity Research From Ce...mentioning
confidence: 92%
See 1 more Smart Citation
“…Other innovations in the structure of the clinical trials system will be necessary to truly foster diversity and representativeness, including decentralization of research to locations near patients of color 100 . In a recent analysis of accrual patterns by race for a large breast cancer cooperative group trial that oversamples Black women, we found that the most important site-level predictor of high accrual of Black patients was the proportion of Black residents in the zip code where the trial site was located 101 . Other key strategies, as outlined in a recent policy statement from the American Society of Clinical Oncology and Association of Community Cancer Centers, include education of the research workforce on equity, diversity, and inclusion issues and diversifying the workforce itself to reflect the communities in which cancer research is performed 102 .…”
Section: Five Keys To Impactful Breast Cancer Equity Research From Ce...mentioning
confidence: 92%
“…100 In a recent analysis of accrual patterns by race for a large breast cancer cooperative group trial that oversamples Black women, we found that the most important site-level predictor of high accrual of Black patients was the proportion of Black residents in the zip code where the trial site was located. 101 Other key strategies, as outlined in a recent policy statement from the American Society of Clinical Oncology and Association of Community Cancer Centers, include education of the research workforce on equity, diversity, and inclusion issues and diversifying the workforce itself to reflect the communities in which cancer research is performed. 102 A large community of breast cancer advocates and survivors exists, including many people of color, which can be leveraged to better represent all patients with breast cancer in clinical trials, if researchers and regulators make this a priority.…”
Section: Create Research Questions and Structures That Center The Nee...mentioning
confidence: 99%